(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
During the wheat crop of 2017-2018, black point disease was studied in 553 samples of wheat grain collected just after harvest in the month of May 2018. The average percent incidence in Agra was found to be 54.6. The maximum incidence (73.0) was recorded from wheat samples collected from Kheragarh tehsil and the minimum incidence (45.2) was noted in samples collected from Karaoli tehsil. study relating to fungi associated with discolored wheat kernels revealed the presence of 11 fungal species, out of which Alternaria alternate showed maximum present incidence and abundance. The next prominent world was Curvularia lunata followed by Alternaria triticina and Helminthosporium naturism. Other fungi of minor importance include Aspergillus flavors, A. ochraceus, A. Niger. Bipolaris sorokiniana Cladosporium herbarium fusarium graniunearum and nigrospors oryzae occur during the harvest period in western U.P including Agra. Therefore, it was considered important to assess seed lots of wheat for the occurrence of black point disease which decreases the quality and germinability of wheat grains.